Development of Problem Based Learning Devices in Two Variable Linear Equation System Materials - Farida Farida; Kartini Kartini; Sehatta Saragih (Universitas Riau, 2021)
The student learning activities do not support developing mathematical problem solving abilities. One of the factors is the learning tools used have not provided the opportunity for students to hone their mathematical problem solving skills. This study aims to produce a valid and practical semester VIII class SMP mathematics learning device for use by using the Problem Based Learning Model with a scientific approach to the SPLDV material. This type of research is a development research with the ADDIE development model which includes the following steps: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. Data were collected through observation, interviews, and student response questionnaires. The subjects of this study were students of class VIII MTS GUPPI Bandar Sungai. Data analysis techniques used qualitative and quantitative statistics. Based on the results of data analysis, information was obtained that the learning device met the valid and practical criteria. The results of the validity of the learning tools in the form of a syllabus with a percentage of 82.99%, RPP 85.75% and LKPD of 83.23% fulfilled the validity level, namely valid. The results of the practicality of the learning tools seen from the student response questionnaire were 92%, these results met the practicality level, which was very practical, while in terms of the teacher's observation sheet it fulfilled the practicality level of 87.78% fulfilling the very practical level.